A simple-designed mobile chat application for elderly people - Zannat, Nahreen; Nowshin, Nadia; Mahmud, Murni (MNNF Publisher, 2021)
In the digital era, the Internet and mobile apps have played a vital key to communication, especially in this pandemic. This study aimed to design an app that overcomes the digital barriers and challenges elderly people face when using a chat application. While the most modern chat apps have a lot of interactive features for more usability, elderly users often struggle to navigate them because of lack of technical capabilities. Making things worse, older model of cell phones and apps are slowly discontinued, leaving them to choose between missing out or straining themselves from using cell phones. Thus, the authors came out with the main objective of this paper: to design a minimalistic and user-centric app specifically for elderly people in order to reduce their digital boundaries and simplify communication with their closed ones or anyone via online calls and text messages. To create a personalised solution for this issue, authors used a human-centred design approach in creating the app. The authors first reviewed relevant existing literatures and existing data, before incorporating the information with the findings from the interview and observing target users. It was found that not only the elderlies have difficulties in complex app, but they also struggle with compact contents, small fonts, and low contrast colours. Responding to these needs, the authors designed a simpler system that provide the basic features to make them feel more comfortable. The app also includes a spacious and accessible layout with essential features such as Profile, Contacts, Call Logs, Text Messages, Emergency, and Star Contacts. It’s easy navigation flow allows users to immediately use the features after a quick sign-up. Authors It is expected that this elderly-centred designed app will create a unique platform for elderly people to engage.